Pendidikan Berbasis Komunitas untuk Lansia di Era Digital: Pendekatan Psikologi Positif - Camelia Bakker; Apriyanto Apriyanto; Rahman Tanjung; Syamsul Anwar; Andro Ruben Runtu (Departement of Mathematics Education, 2024)
This study highlights the challenges faced by the elderly in the digital era, particularly regarding feelings of marginalization and difficulties in accessing technology. Community-based education that integrates positive psychology approaches can be an effective solution to improve the mental well-being and digital skills of the elderly. A qualitative case study method was employed, involving in-depth interviews, focus group discussions, and participatory observations to explore the experiences and perspectives of the elderly participating in this educational program. The findings show improvements in digital skills, self-confidence, emotional well-being, and social connections among the elderly. Participants felt more connected and supported, which positively impacted their mental health. The study recommends active participation of the elderly in program design and the integration of positive psychology elements to ensure the sustainability of such programs in the future.